P500 Barriers and opportunities for partner services related to syphilis among men who have sex with men in anchorage, alaska. (14th July 2019) - Quilter, Laura; Boyette, Melissa; Brennan, Julia; Harvill, Jessica; Jones, Susan; Llata, Eloisa; Mclaughlin, Joe; Morawski, Bozena; Ridpath, Alison; Smith, Tracy; Tiffany, Amanda; Torrone, Elizabeth; et al.
Abstract : Background: Early syphilis is highly infectious and can lead to life-threatening complications if left untreated. During 2017–2018, early syphilis cases in Alaska tripled from 24 to 76, with most 2018 cases occurring among Anchorage men who have sex with men (MSM). Partner services can mitigate transmission. We conducted an investigation to identify syphilis partner services barriers and opportunities among MSM in Anchorage. Methods: During October 19–November 13, 2018, we administered an anonymous survey to men and transgender women aged ≥18 years residing in Alaska who reported sex with a man during the previous 6 months. The self-administered survey, available online and as paper, asked about knowledge, risk behaviors, medical care-seeking practices, and attitudes regarding syphilis. A convenience sample was recruited from digital platforms (e.g., Facebook ®) and bars, clinics, and community-based organization events. Results: Of 119 survey respondents, 90 (76%) lived in the Anchorage/Mat-Su region. Of these, 10.0% (95% confidence interval [CI]: 5.3–17.9) reported a syphilis diagnosis during the previous 12 months and having a median of 3 (interquartile range: 1–6) sex partners during the previous 6 months. High-risk behaviors commonly associated with syphilis were reported, including condomless anal sex (36.7%; 95% CI: 27.4–47.0) during the previous month, ≥1 episode of group sex (26.7%; 95% CI: 18.6–36.6) during the previous 6 months, and meeting sex partners online or on a geospatial mobile app (66.7%; 95% CI: 56.4–75.5) during the previous 6 months. Additionally, 44.4% (95% CI: 34.6–54.7) reported a sex partner living outside Anchorage and 31.1% (95% CI: 22.5–41.3) outside Alaska. Conclusion: Large numbers of sex partners outside Alaska presents barriers to partner services among Anchorage MSM with syphilis. Opportunities include using innovative strategies (e.g., technology-based partner services and out-of-jurisdiction partnerships) to reach populations at risk for syphilis. Disclosure: No significant relationships.